2010
DOI: 10.1161/hypertensionaha.109.149369
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Therapy Reverses Large Artery Remodeling and Improves Arterial Compliance in Senescent Spontaneously Hypertensive Rats

Abstract: Abstract-Hypertension and aging are associated with large artery structural remodeling and stiffening, which are known to increase cardiovascular risk. Relaxin is a peptide hormone with potent antifibrotic action in multiple organs. Although relaxin is able to reduce peripheral vascular resistance and improve arterial compliance in rats, it remains unclear whether the improvement in compliance is indirectly attributed to a vasodilatory action or whether relaxin is able to reverse arterial remodeling and stiffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 43 publications
5
59
0
1
Order By: Relevance
“…Furthermore, administration of rhRLX to older RLX Ϫ/Ϫ mice significantly reversed the established fibrosis in lungs, kidneys, and heart (36). Xu et al (52) recently reported comparable results in relaxin-treated senescent spontaneously hypertensive rats, i.e., the hormone increased SMC density and reduced collagen in the aorta.…”
Section: Relaxin-induced Compositional Remodeling Of the Vascular Wallmentioning
confidence: 67%
“…Furthermore, administration of rhRLX to older RLX Ϫ/Ϫ mice significantly reversed the established fibrosis in lungs, kidneys, and heart (36). Xu et al (52) recently reported comparable results in relaxin-treated senescent spontaneously hypertensive rats, i.e., the hormone increased SMC density and reduced collagen in the aorta.…”
Section: Relaxin-induced Compositional Remodeling Of the Vascular Wallmentioning
confidence: 67%
“…However, in patients not receiving angiotensin converting enzyme inhibitors, inhibition of cyclooxygenase had little effect on the vasodilator response to relaxin (Fisher et al, 2002). The vasodilator mechanisms suggested for relaxin in both humans and in animal models involve activation of NOS (Nistri and Bani, 2003;, VEGF, placental growth factor (PGF), matrix metalloproteinases, ET B receptors (Novak et al, 2002;Dschietzig et al, 2003), and modification of the extracellular matrix of the vessel walls (Jeyabalan et al, 2003;Lekgabe et al, 2005;Xu et al, 2010;McGuane et al, 2011b). These responses have a distinct temporal hierarchy.…”
Section: Physiologic Roles Of Relaxin Family Peptide Receptors Andmentioning
confidence: 99%
“…Along this line of thought, RLX was shown to improve the grafting and antifibrotic efficacy of stem cell therapy for organ repair in various in vivo models (Formigli et al, 2007;Bonacchi et al, 2009;Huuskes et al, 2015). The possibility that RLX may be therapeutically effective in COPD is further supported by the results of an experimental in vivo study on age-related vascular damage, which have shown that RLX treatment possesses the unique ability to not only prevent but also revert established arterial remodeling and fibrosis (Xu et al, 2010).…”
Section: Discussionmentioning
confidence: 97%